Comparative Analysis of Adaptation of Conventional and Printable Complete Denture Bases to the Underlying Casts - An In vitro Stereomicroscopic Study - Divyansh Sinha; Keerthi Sasanka Lakkoji; Nadhirah Faiz (Indian Journal of Dental Research)
Introduction: Properly adapted complete denture bases will have adequate retention to the underlying oral mucosa. With technological advancement, there are various techniques of fabrication of complete dentures. There are studies regarding the marginal adaptation of conventional and CAD-CAM denture bases, but there is not enough research comparing the marginal adaptation and polymerisation shrinkage of conventional and 3D printed complete denture bases. Study Setting and Design: In vitro study using stereomicroscopy to determine the marginal discrepancy between the denture base and the cast. Materials and Methods: Twelve gypsum casts were taken and divided into conventional and 3D-printed groups. Conventional denture bases were fabricated by adapting wax of 2 mm thickness which was subsequently processed whereas 3D printed bases were designed and the standard tessellation language (STL) files were used to print the denture bases. Three points were marked at the mid-palatal line and on both maxillary tuberosities. Digital images were then captured at the marked regions and were used to measure the maximum gap between the cast and denture base at the marked regions. Data were analysed using an independent t-test and one-way ANOVA. Results: Conventional dentures had a significantly lesser marginal discrepancy than 3D printed dentures (P = 0.000). The left maxillary tuberosity showed the highest marginal discrepancy, significantly different from mid-palatal and right tuberosity sites. Conclusion: Conventional dentures perform better than their counterparts in terms of adaptation. This accurate adaptation is vital for the retention of the complete denture.